2018
DOI: 10.3390/mi9050205
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characteristics of MAPbBr3 Perovskite Quantum Dots on NiOx Film and Application for High Transparent Solar Cells

Abstract: In this work, a MAPbBr3 quantum dot (QD-MAPbBr3) layer was prepared by a simple and rapid method. Octylammonium bromide (OABr) gives the MAPbBr3 better exciton binding energy, good surface morphology, and stability. To form a nanocrystalline thin film on indium tin oxide (ITO) glass, the QD-MAPbBr3 film was coated by a spin-coating method in a nitrogen-filled glove box and the NiOx film was used as an adhesive layer and hole transport layer. The highest transmittance of MAPbBr3 on NiOx/ITO glass was around 75%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Although most early research studies were focused on bulk thin film perovskites, very recently there has been a growing interest in exploring perovskite nanocrystals (NCs) for various applications due to their enhanced stability in the presence of ligands . Several studies have already shown that perovskite NCs possess great potential for solution‐processable photovoltaic devices under ambient atmosphere due to their high environmental and thermodynamic stabilities . Other studies demonstrate the charge transfer dynamics for perovskite NCs in heterojunctions showing great potential for charge extraction in further applications .…”
Section: Responsivity (R) and Detectivity (D*) Of Photodetectors Undementioning
confidence: 99%
“…Although most early research studies were focused on bulk thin film perovskites, very recently there has been a growing interest in exploring perovskite nanocrystals (NCs) for various applications due to their enhanced stability in the presence of ligands . Several studies have already shown that perovskite NCs possess great potential for solution‐processable photovoltaic devices under ambient atmosphere due to their high environmental and thermodynamic stabilities . Other studies demonstrate the charge transfer dynamics for perovskite NCs in heterojunctions showing great potential for charge extraction in further applications .…”
Section: Responsivity (R) and Detectivity (D*) Of Photodetectors Undementioning
confidence: 99%
“…Hybrid organic-inorganic perovskite materials have been widely accepted and applied in solar cells. The power conversion efficiency has evolved from 3.8% in 2009 to a certified value of 22.7% in 2018 [1,2,3,4,5]. Perovskite materials are a versatile material with unique optoelectronic properties, exhibiting strong light absorption, long diffusion length, and high mobility [6].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the precursor solution was added into 3 mL of chloroform under vigorous stirring at 90 °C to obtain highly luminescent perovskite QDs with a green color. 40 The perovskite QDs were collected by centrifugation and cleaned several times with hexane to remove the residue. The QDs were suspended in toluene to form a 0.1 wt % solution for the QD layer preparation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thereafter, oleic acid (0.4 mL) and oleylamine (0.2 mL) were added to the solution with continuous stirring at 60 °C. Then, the precursor solution was added into 3 mL of chloroform under vigorous stirring at 90 °C to obtain highly luminescent perovskite QDs with a green color . The perovskite QDs were collected by centrifugation and cleaned several times with hexane to remove the residue.…”
Section: Methodsmentioning
confidence: 99%